Danishness in Carl Nielsen’s ’folkelige’ Songs - Vestergård, Karen; Vorre, Ida-Marie (Carl Nielsen Studies, 2008)
Nielsen’s ’folkelige’ songs have been linked in many contexts with something especially Danish. In this article we deal with how this perception has arisen — from the composer’s declared intentions, from the practice of communal singing, and from their literary reception. As an introduction we sketch certain central lines in the history of ’folkelig’ communal singing. With a view to evaluating the composer’s intentions we then outline the main points from our interpretations of Nielsen’s own statements and our analyses of text, music and their interaction, using the selection of Nielsen’s songs to be found in the Folk High School Songbook (1993). From this it is concluded that in his own way Nielsen may be said to have had the intention to give his folkelige songs a ‘Danish’ character.